New experimental insights for better parameter estimation and modelling of concrete at early ages - Azenha, Miguel (2015)
[Excerpt] The numerical simulation of concrete behaviour at early ages is fundamental for an adequate prediction/understanding of the service life behaviour of structures. Indeed, relevant initial stresses (or even cracking) can be induced due to volumetric changes that are particularly significant in this initial time frame. In view of these important phenomena, the simulation strategies for massive concrete structures with NSC normally encompass multi-physical frameworks, in which it is usually enough to consider a thermo-mechanical analysis. Nonetheless, relevant challenges exist in what concerns to the adequate material characterization. In fact, there are several properties for which the normally available testing techniques do not provide fully adequate characterization potential. In such cases, modelling tends to have simplified assumptions. The present work intends to provide an integrated overview of the approaches adopted by this research team, particularly emphasizing original techniques that bring added value to the accuracy and reliability of simulations. The work therefore focuses on four main issues of concrete characterization: (i) thermal dilation coefficient (TDC); (ii) E-modulus; (iii) creep behaviour; (iv) behaviour under restrained deformation. The presentation focuses on the overall description of newly developed methodologies and their inherent advantages. [...]